Analisis Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Guru SD Negeri di Kecamatan Tebing Tinggi Timur - Suwardi Suwardi; Sudarno Sudarno; Aminuddin Zuhairi (Instructional Development Journal, 2022)
Teacher performance is an important factor in the implementation of learning which is an indicator of the achievement of learning objectives. The better teacher performance will have a good impact on the achievements in the learning process. Achieving maximum teacher performance is influenced by various factors. As a member of an organization, namely a school, teacher performance is influenced by leadership style, work motivation and work environment. The purpose of this study was to determine whether there is an influence between leadership style, work motivation and environment on the performance of teachers in public elementary schools in Tebing Tinggi Timur District, Kepuluaan Meranti Regency. This research is a quantitative study with a survey research method approach. The population in this study consisted of 12 schools with a total sample size of 57 people. The data analysis technique in this study uses path analysis techniques, data processing involves the SPSS (Statistical Product and Service Solutions) application. The pattern of influence between these four variables is expressed by the regression equation Ẑ=-9.862+0.402X1+0.384X2+0.393X3 which provides information that the constant of -9.862 states that if there is no increase in the value of the leadership style variable (X1) work motivation (X2) and work environment (X3) then the value of teacher performance (Z) is -9.862. The multiple regression coefficient of 0.402; 0.384 and 0.393 states that each addition of one score of leadership style, work motivation and work environment will provide an increase in value of 0.280; 0.324 and 0.464 in teacher performance. The magnitude of the contribution of leadership style, work motivation and work environment simultaneously that directly affects performance is R2 = 0.676 x 100% = 67.6%. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//